Sensitivitas Bibit Jewawut (Setaria Italica (L.) P. Beauv) di Lahan Salin Pantai Cilacap - Yugi R. Ahadiyat; Normawati Normawati; Totok Agung Dwi Haryanto (Politeknik Negeri Lampung., 2020)
The objectives of this study were to determine the criteria of foxtail millet seedlings in coastal area and the effects of N, P, K fertilizer and water hyacinth ameliorant powder on growth characters of young foxtail millet plant in coastal saline land. The study was conducted at south coast, Bunton Village, Adipala District, Cilacap Regency in May-October 2019. Study in coastal saline land with factorial Randomized Complete Block Design with four replications. The treatment consisted of two factors, namely the dosage of N, P, K fertilizer (N, P, K = 25%, 50%, 75%, and 100% recommended dosage) and the water hyacinth powder ameliorant dose i.e. Â 0 t / ha, 1.5 t / ha and 2.5 t / ha. Observation variables on seedling morphology viz. seedling height, leaf length, stem diameter, number of leaf and leaf greenness, and on.the field viz. plant height, number of leaf, fresh and dry root weights, total root length, and fresh and dry shoot weights. The results showed that good seedling criteria was. Plant heightÂ (24-26 cm), leaf length (15-17 cm), leaf number (3-6), stem diameter (3,2-3,6 cm) and leaf greeness (18,6-20,9 unit). Application of fertilizer dosages of N, P, K 50% + without ameliorant gained the greater plant height of 62.76 cm and number of leaf of 7.28 than other treatments